The Design of UV Absorbing Systems for Horticultural Applications. (24th September 2013) - Mahendra, V.; Davis, F. J.; Hadley, P.; Gilbert, A.
Abstract : The synthesis and fluorescence behavior of a series of bis(trisilylalkyl)anthracene molecules is described. The photodegradation of these molecules under UV light has been monitored and compared to a commercially available fluorescent optical brightener. There is a relationship between the structure and the rate of photo decay. The materials with more bulky substituents exhibit the greater stability towards UV. For bis(triphenylsilyl)anthracene the photostability appears to be comparable with a commercially available optical brightener, but the molecule may be susceptible to thermal decay.